Bread, freedom, social justice : workers and the Egyptian revolution - Alexander, Anne, 1974-; Bassiouny, Mostafa (Zed Books, 2014)
Provides an in-depth account of the emergence of independent trade unions and workers' militancy during Mubarak's last years in power and their destablising impact on the post-revolutionary regimes.